Critical role of the miR‐200 family in regulating differentiation and proliferation of neurons. (June 2015) - Pandey, Ankita; Singh, Parul; Jauhari, Abhishek; Singh, Tanisha; Khan, Farah; Pant, Aditya B.; Parmar, Devendra; Yadav, Sanjay
Abstract: The generation of differentiated and functional neurons is a complex process, which requires coordinated expression of several proteins and microRNAs (miRNAs). The present study using nerve growth factor (NGF)‐differentiated PC12 cells led to the identification of miR‐200, miR‐221/222 and miR‐34 families as major up‐regulated miRNAs in fully differentiated neurons. Similar to PC12 cells, induction of miR‐200 family was observed in differentiating neural stem cells, demonstrating a direct role of miR‐200 family in neuronal differentiation. Over‐expression of miR‐200 induced neurite formation in PC12 cells and regulated neuronal markers in favour of differentiation. However, inhibition of miR‐200 induced proliferation of PC12 cells. In differentiating PC12 cells and neural stem cells, an inverse relationship was observed between expression of reprogramming transcription factors (SOX2, KLF4, NANOG, OCT4 and PAX6) and miR‐200. Over‐expression of miR‐200 in PC12 cells significantly down‐regulated mRNA and protein levels of SOX2 and KLF4. Moreover, we observed two phases of dramatic down‐regulation of miR‐200 expression in developing rat brains correlating with periods of neuronal proliferation. In conclusion, our results indicate that increased expression of the miR‐200 family promotes neuronal differentiation, while decreased expression of the miR‐200 family promotes neuronal proliferation by targeting SOX2 and KLF4. Abstract : Nerve growth factor‐induced differentiation of PC12 cells produced maximum induction in the miR‐200 family. Over‐expression of miR‐200 initiated differentiation in PC12 cells and downregulated SOX2 and KLF4 genes. Moreover, similarities observed in expression patterns of miR‐200 and their targets between differentiating PC12 and neural stem cells (NSCs) suggest that PC12 cells can be used in place of NSCs.